Comparison of ocular manifestations in diabetic vs. non-diabetic patients in southern Rajasthan - Mali, Pratiksha; Mehta, Rishi; Patel, Aval (International Journal of Research in Medical Sciences, 2022)
Background: Effects of DM are gradual, progressive and due to chronic exposure to high blood sugar levels. DM also affect the eyes which can lead to ocular morbidity as DR can cause blindness. In that view, it becomes increasingly important to diagnose them at the earliest for proper management and prevention of complications. Methods: A total of 182 patients examined, out of which 91 were diabetic and 91 were non diabetic. Complete ocular examination was done that included visual acuity, anterior segment and fundus. Diabetic retinopathy was graded according to ETDRS classification. Diabetic patients were divided into 3 groups on the basis of HbA1c level (%): group-A (6-8), group-B (8-10) and group-C (>10). Patients were divided into 3 groups on the basis of duration (years): group1 (<5), group-2 (5-10) and group-3 (>10). Results: Ocular manifestations were more prevalent in diabetics than non-diabetics along with that DR was found in diabetic patients and no retinopathy was found in non-diabetic patients. Out of 91 diabetic patients, DR was found in 30(33.3%) patients. Out of 30 DR, NPDR was found in 25(75%) and PDR was found in 5 (15%). DR in group A, B and C: 0, 17 (58%) and 13 (86%) respectively. DR in group1,2 and 3 was 3 (7.5%), 11 (35.4%) and 16 (80%) respectively. Conclusions: Longer duration of diabetes and higher HbA1c level are associated with increased prevalence and severity of DR.